[PP.28.11] MASKED HYPERTENSION IN OBSTRUCTIVE SLEEP APNOEA SYNDROME (OSAS) PATIENTS: NOT SUCH A RARE CIRCUMSTANCE. (September 2016) - Feki, S.; Mssead, S.; Mahfoudh, H.; Chaabouni, Y.; Mnif, K.; Jarraya, F.; Kammoun, K.; Kammoun, S.; Hachicha, J.
Abstract : Objective: OSAS is a recognized as a risk factor for development of cardiovascular diseases and hypertension. Hypertension is observed in 1/3 of OSAS. This last is recognized cause of secondary resistant hypertension. The objective of this study is to assess the prevalence of masked hypertension in patients with OSAS. Design and method: We carried out a prospective study of consecutive patients with OSAS confirmed by polysomnography. All patients underwent blood pressure (BP) measurement and 24 h blood pressure monitoring (ABPM). Masked hypertension is defined as office blood pressure< 140/90 while outside daytime ambulatory blood pressure averages are >135/85. Results: We enrolled 19 patients with sex ratio of 1.7. Average age was 50 ± 14 years. Cardiovascular factors were: diabetes (21%) dyslipidemia (16%), tobacco (31%), and treated hypertension 9 cases (47%). OSAS was severe in 18 cases. Mean average daytime and nighttime BP were respectively 147.8/94.75 mmHg and 137/77 mmHg. Thirteen patients had masked hypertension. All patients had a non dipper profile (nighttime fall of mean nighttime BP <10%). Conclusions: To our knowledge only a limited number of studies investigating the prevalence of MH in patients with OSAS exist. This study highlights that masked hypertension is frequent in OSAS population. In literature MH is observed in 50–60% of OSAS. ESH guidelines for management of patients with OSAS and hypertension recommend using ABPM or home monitoring usage to diagnosis MH or nighttime HT.